POTENSI AIRTANAH BERDASARKAN KARAKTERISTIK AIRTANAH PADA SETIAP SATUAN HIDROMORFOLOGI DI CEKUNGAN AIRTANAH PALU - Zeffitni, Zeffitni (MEKTEK, 2010)
Water availability for various need are decreasing qualitatively and quantitatively, while on the other hand, water demand is increasing, thus, water management problem always occurs. This phenomenon is also found at Palu Groundwater Basin, Central Sulawesi Province, especially at Palu City. The distribution of groundwater potential, which has the spatial and temporal characteristics, caused insufficient domestic needs at Palu City. Thus, according to the problem, the research objectives to analyze groundwater potential based on groundwater characteristics on each hydromorphology units.The research method is survey method as a basis for spatial and ecological analysis, with landform and geology condition as a basis to determine groundwater sample point. Data analysis method in this research consists of: the analysis for field data and analysis for hypothesis testing. Field data analysis consists of technical analysis to determine hydromorphology units. Hypothesis testing analysis are done according to research objectives based on spatial and ecological analysis, and integration of geomorphologic and geologic approach.The result of the research shows that: groundwater potential level based on groundwater characteristics are at alluvial plains hydromorphology unit in Alluvium and Pakuli Formation, which distributed from high – medium. The research findings shows that Palu Groundwater Basin are one of the groundwater basin in Palu Basin, formed due to geological structure (Palu Graben), the Palu fault (sesar). The inflow boundary is located at east and west of Palu River, which is from bent slope of structural hills, the Gawalise Mountain and Tanggungguno Mountain. The outflow boundary is located at the north, the Palu Gulf